2007
DOI: 10.1021/ac061379w
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Pressurization To Speed Up Enzymatic Hydrolysis of Biological Materials for Multielement Determinations

Abstract: The feasibility of pressurized solvents (liquids at a high pressure and/or high temperature without the subcritical point being reached) has been newly investigated to accelerate enzymatic hydrolysis processes of mussel tissue for multielement determinations. The target elements (Al, As, Cd, Co, Cu, Fe, Hg, Li, Mn, Pb, Se, Sr, V, and Zn) were released from dried mussel tissue by action of two proteases (pepsin and pancreatin), and they have been evaluated by inductively coupled plasma optical emission spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 17 publications
(30 reference statements)
1
29
0
Order By: Relevance
“…The developed process was preferred over more conventional extraction/hydrolysis processes based on methanol extraction and hydrochloric acid hydrolysis at 80°C, regarding primary energy consumption and global warming potential (Lindahl et al 2010 ) . Following a similar approach, integrated treatments considering enzymatic hydrolysis plus extraction carried out on different algae, such as Hizikia fusiformis (164), Ecklonia cava, and other brown algae (Athukorala et al 2006 ;Moreda-Piñeiro et al 2007 ;Turner et al 2006 ;Heo et al 2005 ) could be optimized in a more effi cient and Green way using the abovementioned concepts and ideas. Moreover, studies have demonstrated that processes such as enzymatic hydrolysis are accelerated under pressure conditions, thus giving even stronger support to the possibility of improving the processes through the use of integrated pressurized fl uid technologies (Moreda-Piñeiro et al 2007 ) .…”
Section: From Analytical To Industrial Scale: Multiple Integrated Promentioning
confidence: 99%
“…The developed process was preferred over more conventional extraction/hydrolysis processes based on methanol extraction and hydrochloric acid hydrolysis at 80°C, regarding primary energy consumption and global warming potential (Lindahl et al 2010 ) . Following a similar approach, integrated treatments considering enzymatic hydrolysis plus extraction carried out on different algae, such as Hizikia fusiformis (164), Ecklonia cava, and other brown algae (Athukorala et al 2006 ;Moreda-Piñeiro et al 2007 ;Turner et al 2006 ;Heo et al 2005 ) could be optimized in a more effi cient and Green way using the abovementioned concepts and ideas. Moreover, studies have demonstrated that processes such as enzymatic hydrolysis are accelerated under pressure conditions, thus giving even stronger support to the possibility of improving the processes through the use of integrated pressurized fl uid technologies (Moreda-Piñeiro et al 2007 ) .…”
Section: From Analytical To Industrial Scale: Multiple Integrated Promentioning
confidence: 99%
“…The reactors were then subjected to a conventional microwave program [40]. After acid digestion was completed, the acid digests were made up to 25 mL with ultra-pure water.…”
Section: Microwave Assisted Acid Digestionmentioning
confidence: 99%
“…A similar effect can be obtained when assisting enzymatic hydrolysis by pressurization. Thus, Moreda-Piñeiro et al [38] have proved the feasibility of pressurization (pressurized liquid extraction, PLE) to speed up enzymatic hydrolysis of marine biota (mussel), fatty biological tissues and plants for total metal extraction. The pre-treatment time was shortened to 6 min (3 PLE cycles of 2 min each one at 50 • C and 1500 psi) using pepsin or pancreatine as proteases.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, developing a sensitive, selective, highly precise, and economical analytical method for the monitoring of silver in environment samples with complex matrices is required. There are many sensitive but expensive analytical methods such as electrochemical analysis, 3 inductively coupled plasma mass spectrometry 4 and electrothermal atomic absorption spectrometry. 5 In addition, these instrumental techniques involve complicated processing step.…”
Section: Introductionmentioning
confidence: 99%